Do stand-alone CSR reporting, assurance and the use of GRI guidelines correlate with the quality of CSR disclosure? Empirical evidence from Nordic utility companies - Verkasalo, Linda (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
Despite the increasing focus on corporate social responsibility (CSR), most of the research on disclosure quality has not found good proxies for quality and thus the quality of disclosure remains uncertain. Also, potential determinants of good quality disclosure have not been identified. In order to fill in some of the gaps in previous literature, this study aims to find out whether issuing a stand-alone CSR report, assuring the CSR disclosure and using Global Reporting Initiative (GRI) guidelines are correlated to CSR disclosure quality in Nordic utility companies. The potential change in CSR disclosure quality between 2013 and 2015 is also investigated. Moreover, the disclosure quality is captured with four complementary proxies in order to gain a more reliable and comprehensive grade for quality rather than relying on a simple word count method. The proxies used to measure CSR disclosure quality in this study are density, accuracy, managerial orientation and versatility. Content analysis is adopted and the results are analyzed in accordance with stakeholder theory. It was found that stand-alone report was positively and significantly correlated with CSR disclosure quality indicating that the stakeholders of Nordic utility companies may expect the stand-alone reports to be of better quality than the CSR sections in the annual reports. In practice this means that stakeholders of utility companies may expect the stand-alone reports to be more valuable. This also suggests that Nordic utility companies may be relatively active in CSR. On the other hand, assurance and the use of GRI guidelines were not associated with CSR disclosure quality so CSR disclosures of Nordic utility companies are not necessarily more valuable in the presence of those practices. All the companies used financial auditors, however, who do not possess the specialized knowledge for adding value to CSR disclosure. The relation of GRI should be studied with a different method before any conclusions are drawn. The findings support the existing CSR literature by hinting that companies may adopt reporting practices as a response to stakeholder pressures and that reporting practices may be used by companies as PR tools. For this period of time, no significant change in quality was detected indicating that the stakeholders may be satisfied with the current level of quality. In practice this finding also suggests that the primary stakeholders of Nordic utility companies are not necessarily relying on CSR disclosures to learn about the companies’ responsibility – they already know the company can direct its resources elsewhere than perfecting the CSR report.